2014
DOI: 10.1002/jclp.22113
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Related Treatments For Mental Disorders Lack Empirical Support: A Systematic Review of Empirical Investigations

Abstract: The current evidence base does not justify the marketing and utilization of ERT for mental disorders. Such services should not be offered to the public unless and until well-designed studies provide evidence that justify different conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 28 publications
0
51
0
7
Order By: Relevance
“…With the growing state of research, empirical and theoretical, a cautionary measure of using EFT as a complementary intervention, or for those who are not reached by conventional methods (Lentini & Knox 2009) seems far more reasonable than avoiding the intervention outright until data confirms its effect (Anestis et al 2014).Within social work, attachment theory, inclusive of transitional object theory and holding theory, provides a foundation to explain and predict the anticipated outcomes of EFT; facets of a strong theoretical framework. Thus, attachment theory can therefore guide more rigorous inquiry to evaluate effects in mental health treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing state of research, empirical and theoretical, a cautionary measure of using EFT as a complementary intervention, or for those who are not reached by conventional methods (Lentini & Knox 2009) seems far more reasonable than avoiding the intervention outright until data confirms its effect (Anestis et al 2014).Within social work, attachment theory, inclusive of transitional object theory and holding theory, provides a foundation to explain and predict the anticipated outcomes of EFT; facets of a strong theoretical framework. Thus, attachment theory can therefore guide more rigorous inquiry to evaluate effects in mental health treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The authors conclude with "…we recommend, in view of the current evidence vase, individuals in need of mental health services avoid seeking out EFT and treatment centers avoid practicing this approach… until a strong research foundation for this treatment emerges" (p. 1129). Anestis et al's (2014) claim that EFT should be avoided is extreme; rather than supporting further research, they establish barriers to the field. Though caution is warranted, the research is growing and findings do support the implicit and explicit benefits of AAT (Nimer & Lundahl, 2007;O'Haire et al, 2015), and specifically HAI (Krob, 2015).…”
Section: The Need For Theory-based Research and Practicementioning
confidence: 99%
“…Although a recent review questions the benefits of hippotherapy in mental illness (3), some reports indicate that hippotherapy has a positive effect on patients with mental illnesses and mental disorders. Interaction with horses had a positive impact on the alleviation of aggression and improved interpersonal interaction both during hospitalization of patients with recent in-hospital violent behavior or highly regressed behavior enrolled in this study and few months after release to home care (4).…”
Section: Introductionmentioning
confidence: 99%
“…Hippotherapy is defined as "equine-assisted therapy" for patients with physical and cognitive disabilities (Anesti et al, 2014). It has a wide range of applications and intended populations, and experts in various fields have tried to demonstrate its efficacy (Hession et al, 2014;Anesti et al, 2014;Seo, 2012).…”
mentioning
confidence: 99%
“…It has a wide range of applications and intended populations, and experts in various fields have tried to demonstrate its efficacy (Hession et al, 2014;Anesti et al, 2014;Seo, 2012). In terms of outcomes reported by previous studies, Kwon et al (2015) found that hippotherapy improved gross motor function in children with cerebral palsy, and Lee and Jeong (2005) reported that indoor horseback riding exercise was effective in improving stamina, blood lipid concentration, and bowel satisfaction.…”
mentioning
confidence: 99%